2021
DOI: 10.3390/dj9050053
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors Affecting the Usage of Digital and Social Media: A Preliminary Qualitative Study in the Dental Profession and Dental Education

Abstract: Aims: This study aimed to identify the risk factors of using DSM to provide an insight into the inherent implications this has on dental professionals in practice and trainee professionals’ education. Materials and methods: Twenty-one participants (10 dental professionals and 11 undergraduate and postgraduate dental students) participated in this qualitative study using semi-structured interviews in a dental school in the UK. The interviews were analysed and categorised into themes, some of which were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…14,15,21 Secondly, the interview transcripts from the previous qualitative study by the authors were revisited to identify the pertinent phrases that could form a relevant questionnaire item. 22 These identified F I G U R E 1 A flow chart of key steps in designing the study phrases were reworded to fit the purpose of the questionnaire.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…14,15,21 Secondly, the interview transcripts from the previous qualitative study by the authors were revisited to identify the pertinent phrases that could form a relevant questionnaire item. 22 These identified F I G U R E 1 A flow chart of key steps in designing the study phrases were reworded to fit the purpose of the questionnaire.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…These results correspond with a study by Sharka et al, where it was found that the use of social media led to wastage of time and ignorance of performing important tasks at hand. 22 Many dentists in our study believed that as a dentist, it is their responsibility to disapprove and correct such content. To tackle such misinformation, publishing real and authentic news has one of the suggested ways.…”
Section: Discussionmentioning
confidence: 76%
“…Outro estudo realizado com alunos e profissionais da área odontológica demonstrou que os estudantes percebem que as informações encontradas nas redes sociais podem ser questionáveis, por diferirem do que é ensinado em ambiente acadêmico. Da mesma forma, os profissionais reconhecem como a principal limitação do uso dessas mídias a falta da garantia de veracidade do que é publicado, uma vez que não há nenhum filtro que permita diferenciar informações verdadeiras de falsas (Sharka et al, 2021).…”
Section: Resultsunclassified